STUDY OF MARKERS OF ANTIOXIDANT PROTECTION OF THE ORAL CAVITY IN THE ORAL FLUID OF PATIENTS WITH PERI-IMPLANTITIS AGAINST THE BACKGROUND OF THE TREATMENT AND PREVENTION COMPLEX - Adubetska, A.Y.; Shnaider, S.A.; Dienga, A.E.; Yakimenko, D.O.; Tsushko, I.O.; Maslov, V.O.; Pryima, O.A. (World of Medicine and Biology, 2024)
The study was devoted to researching the effect of the treatment and preventive complex on biochemical markers of the antioxidant system in the oral fluid of patients with peri-implantitis. 40 patients with peri-implantitis aged between 25 and 55 years took part in the research. In the oral fluid of patients, the indicator of antioxidant protection of the oral cavity was determined. The therapeutic and prophylactic complex led to a substantial elevation in the antioxidant-prooxidant index, exceeding the levels found in somatically healthy patients after six months of treatment. This antioxidant-prooxidant index elevation suggests a restoration and amplification of non-specific oral cavity resistance, emphasizing the complex’s potential to sustain long-term antioxidant defense in patients with peri-implantitis amid concomitant conditions like periodontitis and atherosclerosis.